Liquid Chromatography-Mass Spectrometry Determination of Oxytocin in Cow Milk - Kumar Baliyan, Praveen; Singh, R.P.; Arora, Saurabh (Asian Journal of Chemistry, 2010)
Oxytocin is a cyclic octapeptide hormone released by the posterior pituitary and having uterotonic and galctagenic activity in mammals. In cows oxytocin is injected to stimulate uterine contractions and allow for easy flow of milk. This study was carried out to validate a method for the determination of oxytocin in cow milk by liquid chromatography-mass spectrometric (LC/MS/MS system). The method was in-house validated in term of detection limit (LOD), quantification limit (LOQ), linearity, sensitivity, accuracy and recovery in milk. Oxytocin was isolated from milk by solid phase extraction followed by extraction with HPLC. Oxytocin was determined by mass spectrometer using turbo ion spray source in the negative mode. The multiple reaction monitoring procedure has been applied and the ion transitions were: m/z 1005 > 939 (for quantification) and 1005 > 489 (for qualification). It was found out that oxytocin can be quantitated and confirmed at the 1 IU/L level in milk. At these levels trueness ranged between 85 to 101 % and reproducibility was lower than 15 % expressed as RSD. The limit of detection (LOD) and limit of quantification of this method were 1.0 IU/L, 2.0 IU/L respectively.